STRUCTURAL EVALUATION FOR FLEXIBLE PAVEMENT BASED ON AASHTO 1993 AND AUSTROADS 2011 METHOD (CASE STUDY: EASTERN LINK OF SUMATRA HIGHWAY, TEMPINO - BATAS SUMSEL SECTION) - PARDIARINI, DWI
The structural evaluation for flexible pavement is an important phase to determine existing pavement structural condition, and will become a base to decide the maintenance program to preserve the treatment level of road or pavement. Main objective of the study is to evaluate the existing flexible pavement carried out using deflection data from FWD’s (Falling Weight Deflectometer) measurement, case study was chosen between road network in Eastern Link of Sumatera Highway, i.e from Tempino to South Sumatera provincial line. The AUSTROADS 2011 method introduced to use for analyzing this road as comparison from AASHTO 1993 method that has been known before. The AASHTO 1993 methods used FWD’s deflection data to calculate the subgrade resilient modulus (MR) and the effective modulus (Ep) of the existing pavement. The overlay thickness resulted using this method, was variated between 4 cm to 16 cm, depends on value of SNeff (Structural Number Effective) for each segment that evaluated. The FWD’s deflection data was used also as an input in the AUSTROADS (2011)’s method. The backcalculation procces was carried out to determine the layer moduli of three layer and four layer pavement structure considered, by using the computer program ELMOD. The overlay thickness that determine with mechanistic approach by using CIRCLY program was variated between 0 cm to 5 cm, depends on the model assumptions that carried out at pavement layer. The comparison between these 2 (two) methods i.e AASHTO 1993 and AUSTROADS 2011, shows that the model assumptions of pavement layer conduct with the subbase layer that consider as subgrade or not, plays an important role for determine the overlay thickness. The comparison of overlay thickness, calculated by those two methods, showed that the result using the AASHTO 1993 method was higher than the AUSTROADS 2011 method, especially related to the reviewed model assumptions of pavement layer.